PERAN MANAJEMEN RISIKO UNTUK INDIVIDU DAN KELUARGA DI DESA MOUTONG BARAT - Adnan Malaha; Rita Amini Warastuti; Siti Nurhalisa; Novita Ahmad (Journal of Hulonthalo Service Society (JHSS), 2024)
Risk management is an important approach in identifying, analyzing, and managing various potential risks that can affect the lives of individuals and families. In the context of Moutong Barat Village, many people do not fully understand this concept and how to apply it in everyday life. The purpose of this community service is to increase the understanding of the community in this village about the importance of risk management and provide them with skills in identifying and managing potential risks. This activity involves training that includes basic risk management theory and practical simulations. As a result, the community becomes more aware of the various risks that exist, and is able to apply risk management principles to protect themselves and their families from unwanted losses.